Heat and Mass Transfer in Industrial Biscuit Baking Oven and Effect of Temperature on Baking Time - Rostam Akbari Kangarluei (Journal of Heat and Mass Transfer Research, 2015)
This research deals with heat and mass transfer in biscuit industrial baking ovens. In these ovens, heat reaches biscuits indirectly by radiation, convection and conduction. The method for numerical solution is that we first provide the related equations, then they are discretized by finite difference method (FDM), and finally, after encoding and writing a program for the computer, we run it. The Obtained results indicate that biscuit heat absorption occurs 69 % through radiation, 28% convection and 3 % conduction. This percent of conduction depends on the type of band conveyor. Baking time depends on temperature of the baking chamber. For example, it takes 7 minutes for biscuits to reach 4% of moisture in 2000C.By increasing temperature of the baking chamber, the cooking time is decreased. Based on obtained results, there is a balance between heat   and mass transfer rate. Results obtained from solving the equations indicates that maximum temperature of biscuits reaches 1500C and the highest moisture of baking chamber is almost at the middle of the oven. Vapors generated by this procedure are sent out by several fans, installed inside the baking chamber at the same distance. Simulated data of heat and mass transfer equations are in good agreement with experimental results. Obtained results can be used to control baking time and to production good quality for biscuits.